OPOSISI TEKS ANAK DAN KEMENAKAN KARYA MARAH RUSLI: KAJIAN INTERTEKSTUAL JULIA KRISTEVA - Daratullaila Nasri (Kantor Bahasa Sulawesi Tenggara, 2017)
This paper discusses Marah Rusli’s Anak dan Kemenakan text with opposition concept by Julia Kristeva. Opposition is something unexchangeable and unconditional between two inharmonic, not-complementary, and unsettling groups. This paper was written to observe the opposition in Anak dan Kemenakan text. Data analysis methods used are suprasegmental and intertextuality analysis methods. It’s found that the oppositions in the text can be seen from the aspects of educational, marriage, social class, and mamak’s (uncle) and father’s role in Minangkabau’s matrilineal kinship system. All of those aspects are opposite in thought, attitude, and behavior between the old and the youth. It describes that the people of Minangkabau was starting to enter a renewal which was marked by the appearance of educational institution. Meanwhile,the renewal itself wasn’t completely accepted by the society. Therefore, the oppositions between the old and the youth became unavoidable.